Comparatives in Turkish Sign Language (TİD) - Ozsoy, A. Sumru; Kasikara, Huner (Linguistic discovery, 2018)
This study focuses on the comparative constructions in Turkish Sign Language (TID), the native language of the deaf in Turkey. We show that in terms of Stassen's (2013) typology, TID uses two distinct constructions to express comparison: (i) Conjoined Comparatives, and (ii) Locational Comparatives. The Conjoined Comparative construction consists of two structurally independent clauses (one containing the standard, the second containing the comparee) where the NPs function as subjects of their respective clauses. In Locational Comparative constructions, a single predicate expresses the parameter shared by the participants. The two NPs are located in the signing space by indexing (IX) and body shift. Comparison between the two arguments is expressed by [IX.sub.COMP] (the index of comparison). Given that directionality is one of the means that sign languages use to represent the relationship between verbs and their arguments (Lillo-Martin & Meier 2011) and that the direction of the path movement of the manual sign is determined by the thematic roles of the arguments from the R-locus of the SOURCE argument to the R-locus of the GOAL argument in "backward agreement" contexts (Aronoff et al. 2005), we hold that the directionality of movement in the comparative construction in TID is parallel to the verbal agreement of sign languages.